Odpowiedzi

  • Użytkownik Zadane
2010-02-17T16:29:48+01:00
A) -3 * 2 + 4,5 : 0,5 + (-7)=-6+9-7=-4
b) x + (-12) = -4
x-12=-4
x=8
c) -6x = -9
x=9/6
x=½
d) 4,5*(-1)³+ 1 ½: (-3)=-4,5+3/2*⅓=-4,5+½=-4
1 5 1
2010-02-17T16:31:47+01:00
A) -3 razy 2 + 4,5 : 0,5 + (-7) =-10
b) x + (-12) = -4 - -12 = x = 8
c) -6x = -9 x = 1,5
d) 4,5 razy (-1) do potęgi Trzeciej + 1 i jedna druga : (-3) = -4
2010-02-17T16:37:16+01:00
A)-3*2+4,5:0,5+(-7)=-6+9-7=-4
b)x+(-12)=-4
x-12=-4
x=-4+12
x=8
C)-6x=-9|:(-6)
x=1,5
d)4,5*(-1)3+1,5:(-3)=4,5*(-1)+(-0,5)=(-4.5)-0,5=(-5)